(untitled) (Bangladesh Journal of Botany, 2021)
Effects of salt stress on absorption and distribution of osmotic ions in wheat seedlings were studied with 4 winter wheat varieties under NaCl stress by exploring dynamic changes of Ca2+, K+, Na+, Ca2+/Na+, K+/Na+ and Na+ limiting ability. The results showed that the contents of K+, Ca2+ and the K+/Na+ ratio gradually decreased in a manner of both salt concentration dependent and stress time dependent. The extent of reduction of K+ and Ca2+ in root was much more severe than that in shoot. The ability of Na+ limiting in QM6 and DK961 was stronger than that in JM22 and QF1. These results indicate that the maintenance of higher Na+ content in root, Na+ limiting ability, Ca2+ and K+ concentration will be the main physiological traits for the salt-tolerance of wheat. Bangladesh J. Bot. 50(4): 1209-1214, 2021 (December)